The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1177/1049732314542808
|View full text |Cite
|
Sign up to set email alerts
|

Mary’s Little Worlds

Abstract: With the case study presented in this article we explore how people with dementia experience and use their environment to expand our understanding of how architectural environments can improve their well-being. We focus on how relationships between people and spaces change for people with dementia. Using a qualitative analysis of three in-depth interviews with a woman living with dementia, we obtained an insider's perspective and a rich account of the changes in her life, including her lived experiences and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Coping strategies are mentioned in all 26 studies, including trying to ignore or hide difficulties, using humour, using creative expressions, avoiding stress, maintaining daily structure, staying active, focusing on what they can still do, finding meaningful ways to (re)engage and seeking social and religious support. In several of these studies, a shift in attitude to what was important for them in life is described, for example by paying more attention to ‘little things’ and living in the ‘now’ [ 67 , 73 , 83 , 86 , 88 , 89 , 95 , 101 , 102 , 105 , 110 , 116 , 122 ]. One of the participants voiced this concern as followed: “Take it as it is and live today” [ 100 ] (p. 276).…”
Section: Resultsmentioning
confidence: 99%
“…Coping strategies are mentioned in all 26 studies, including trying to ignore or hide difficulties, using humour, using creative expressions, avoiding stress, maintaining daily structure, staying active, focusing on what they can still do, finding meaningful ways to (re)engage and seeking social and religious support. In several of these studies, a shift in attitude to what was important for them in life is described, for example by paying more attention to ‘little things’ and living in the ‘now’ [ 67 , 73 , 83 , 86 , 88 , 89 , 95 , 101 , 102 , 105 , 110 , 116 , 122 ]. One of the participants voiced this concern as followed: “Take it as it is and live today” [ 100 ] (p. 276).…”
Section: Resultsmentioning
confidence: 99%
“…Such concerns within dementia studies have led to growing interest in a “person-in-environment” approach, driven by a more fluid and dynamic understanding of the person–place relationship (e.g. Blackman, 2006 ; McGovern, 2012 ; Van Steenwinkel et al ., 2014 ). For instance, in relation to the experience of outdoor and public spaces for people with dementia, Brorsson and colleagues ( 2011 ) draw on the work of the philosopher John Dewey to develop a transactional perspective, arguing that: The environment is not just a physical place; it also embraces social, cultural and political aspects and includes spatial and temporal dimensions.…”
Section: The Importance Of “Lived Place”mentioning
confidence: 99%
“…For instance, Van Steenwinkel et al [ 10 ] conducted a study focusing on how the built environment contributes to a sense of home of older people living in different contexts in Belgium. Van Steenwinkel et al [ 11 ] investigated the sense of home among permanent and temporary residents of nursing homes in The Netherlands. Both studies concluded that a sense of home is a multifactorial phenomenon which is highly influenced not only by the (built) environment, but also by social and personal characteristics.…”
Section: Introductionmentioning
confidence: 99%